Implemtasi Metode Promethee III Untuk Menentukan Calon Penerima Bantuan Langsung Tunai Akibat Pandemi Covid-19 - Silalahi, Herdawini (AMIK STIEKOM SUMATERA UTARA, 2024)
Direct cash assistance or abbreviated as BLT is a government assistance program for providing cash or a variety of assistance used from village funds and for the poor and underprivileged people, this assistance is an activity to handle the impact of the Covid-pandemic. 19 because it can have an impact on side effects on the economy. The funds that will be used for prospective recipients of direct cash assistance will come from village funds to reduce the economic impact of rural areas. The problems that arise at this time, from the covid-19 pandemic that hit the Indonesian nation, make people restless in various regions and cities, which impact on the difficulty of the community's economy due to decreased daily income. In determining candidate participants who are eligible to receive direct cash assistance sourced from village funds. Prospective recipients of direct cash assistance as a criteria for candidates who have lost their jobs, poor families who live in the village concerned. From the results of research on decision support systems using the PROMETHEE III method because this method can be used to find rankings and determine a decision from several criteria where all the data from each criterion obtained can make it easier to determine potential participants who receive direct cash assistance due to the pandemic covid-19